Teologi Pembebasan Masyarakat Sekuler: Refleksi Pemikiran Harvey Cox - Mohammad Nuh Hasan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2004)
This article examines the background of the emergence of liberation theology within secular society. The rapid advancement of Western civilization, particularly its profound impact on value systems and religion, has become a topic of discussion in Christian theology, as Christianity is the religion most closely associated with the development of modern Western society. Conservative theologians view such phenomena as inherently negative and continue to uphold orthodoxy. Meanwhile, some taking a liberal approach see it as a positive reality. The process of secularization is not viewed as inherently antagonistic to the existence of religion, but rather as a sign of progress in human consciousness that is fundamentally rooted in the Bible. Figures such as Friedrich Gogarten, Rudolf Bultmann, John A.T. Robinson, and Dietrich Bonhoeffer, including Harvey Cox, belong to the latter group. Among these figures, Harvey Cox is the most outspoken proponent of secularization theology, particularly in his monumental work: “The Secular City: Secularization and Urbanization in Theological Perspective” (1965).